Study Block Brick Materials on Base Cotton Stalk and its Properties - Abidjon, Tillayev; Haqberdi, Berdiyev (European Journal of Life Safety and Stability (2660-9630), 2022)
Block bricks based on cement and wood chips are distinguished by energy saving, low cost, environmental friendliness, availability of existing equipment for production. All processes consist of the process of crushing wood products, mixing them in certain proportions, shaping and drying in block filling machines. The product proved to be light, durable and non-flammable. One disadvantage is that it must be stored for at least 30 days after production in order to have sufficient strength.